Vaccination Strategies for SIR Vector-Transmitted Diseases - Cruz-Pacheco, Gustavo; Esteva, Lourdes; Vargas, Cristobal (Bulletin of mathematical biology, 2014)
Vector-borne diseases are one of the major public health problems in the world with the fastest spreading rate. Control measures have been focused on vector control, with poor results in most cases. Vaccines should help to reduce the diseases incidence, but vaccination strategies should also be defined. In this work, we propose a vector-transmitted SIR disease model with age-structured population subject to a vaccination program. We find an expression for the age-dependent basic reproductive number R 0 , and we show that the disease-free equilibrium is locally stable for R 0 ≤ 1 , and a unique endemic equilibrium exists for R 0 > 1 . We apply the theoretical results to public data to evaluate vaccination strategies, immunization levels, and optimal age of vaccination for dengue disease.